Post Tonsillectomy Secondary Haemorrhage Cold Versus Hot Method (Journal of Rangpur Medical College, 2026)
Background: Tonsillectomy is a frequently performed otolaryngological procedure for recurrent infections or obstructive symptoms. The surgical technique may affect bleeding risk. Objective: The study aimed to compare post-tonsillectomy secondary haemorrhage incold versus hot tonsillectomy techniques. Methods: This prospective study was conducted at an otolaryngology unit in North Bengal Medical College & Hospital, Sirajganj, Bangladesh on 90 consecutive patients underwent tonsillectomy or adenotonsillectomy, from January, 2023 to December, 2023, 45 by cold steel dissection and 45 by hot electrosurgical technique. Baseline factors and preoperative Hb and platelet counts were recorded. Results: Both groups were comparable in demographics and baseline clinical factors, including indication, recent URTI, NSAID exposure, hemoglobin, and platelet count (all p>0.05). Haemostasis differed significantly: ties were used more in the cold group (48.9% vs 13.3%) and bipolar diathermy more in the hot group (75.6% vs 40.0%) (p